FORMATION OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE IN STUDENTS OF ECONOMICS - Решетняк, Ірина (SWorldJournal, 2025)
The article considers the concept of communicative competence and identifies its main components, stressing the importance of foreign language communicative competence formation as the final goal of language learning. It also describes the stages of forei